2012
DOI: 10.1016/j.joen.2012.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Mineral Trioxide Aggregate–Resin Modified Glass Ionomer Cement Interface in Different Setting Conditions

Abstract: Introduction Mineral trioxide aggregate (MTA) has been used successfully for perforation repair, vital pulpotomies, and direct pulp capping. However, little is known about the interactions between MTA and glass ionomer cement (GIC) in final restorations. In this study, 2 null hypotheses were tested: (1) GIC placement time does not affect the MTA-GIC structural interface and hardness and (2) moisture does not affect the MTA-GIC structural interface and hardness. Methods Fifty cylinders were half filled with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 28 publications
(37 reference statements)
1
35
1
Order By: Relevance
“…Immediately after molding, the samples were cured in a humidity chamber at 100% relative humidity at a constant temperature of 37 °C for 24 h. At the end of the moist curing period the samples were demoulded and then cured under the two types of aqueous solutions (distilled water and saliva) until the time of testing such as 1, 3, 7and 14 days at a constant temperature of 37°C. The hardness test 20 was carried out on three cubes of each case of the hardened cement pastes. The test was performed with a Vickers indentation hardness tester at five points on one side of each sample.…”
Section: Hardness Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Immediately after molding, the samples were cured in a humidity chamber at 100% relative humidity at a constant temperature of 37 °C for 24 h. At the end of the moist curing period the samples were demoulded and then cured under the two types of aqueous solutions (distilled water and saliva) until the time of testing such as 1, 3, 7and 14 days at a constant temperature of 37°C. The hardness test 20 was carried out on three cubes of each case of the hardened cement pastes. The test was performed with a Vickers indentation hardness tester at five points on one side of each sample.…”
Section: Hardness Testmentioning
confidence: 99%
“…Since this material sets and harden in vivo there is always a certain amount of ion leakage. Earlier studies reported that the leakage and hardness of root end filling materials were all affected over time 20 . The conversion process that is occurred during hydration of CA phase has an adverse effect on physicomechanical properties of hardened CA pastes, namely, bulk density and micro-hardness measurements (Figs.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…In vital pulp therapy using MTA, the choice of restorative material to be applied over MTA is important. Previous studies have emphasized that glass-ionomer cement can be used as intermediate material and that composites can be used for final restoration over MTA [11][12][13] . However, acid etching before composite placement reduces the compressive strength and surface microhardness of MTA 14) .…”
Section: Introductionmentioning
confidence: 99%
“…127 After placing MTA, clinicians can place a wet cotton pellet, dry cotton pellet, 367 or a restorative material above the newly placed MTA. 368 The results of the present study illustrates that using a dry cotton pellet could be detrimental to the strength of the MTA.…”
Section: Discussionmentioning
confidence: 66%